Battered men and our changing attitudes toward intimate partner violence - Perry, Ashley Marie (2014)
The Center for Disease Control (CDC) (2009) estimates that 4.8 million women are victims of intimate partner assault and rape every year. Receiving far less attention in the intimate partner violence literature, however, are studies of the 2.9 million male victims of this type of abuse (CDC 2009). Here I seek to explore this evolving issue of intimate partner violence, and determine to what extent the situations of male victims imitate the abundant body of literature on male violence against women. Using Google’s NGram word corpus (Michel et al. 2010), I examine important changes over time in the usage of the terms commonly associated with intimate partner violence and battering. Of interest is how fluctuation in the usage of these terms in public works correlates with major societal changes such as rights movements and changing laws. Based on what we know of framing of social issues and word choice for fueling social movements, I find that the recent increase of the use of terms associated with male victims has also potentially contributed to the increase in the resources available to aid male victims by increasing public awareness of the problem. Finally, through an online survey of battered men, I find that despite the theory that relationships involving violence against male partners are more often the result of situational fights or mutual couple violence, situations do exist in which males are victims of a manipulative and controlling partner as has often been observed in cases of battered women. In addition to abusers as main aggressors, other similarities to female victims include the use of multiple tactics such as psychological manipulation and insults, verbal abuse, physical abuse and even sexual coercion in order to display dominance or force compliance